Flexure wood formation via growth reprogramming in hybrid aspen involves jasmonates and polyamines and transcriptional changes resembling tension wood development - Urbancsok, János; Donev, Evgeniy N; Sivan, Pramod; van Zalen, Elena; Barbut, Félix R; Derba-Maceluch, Marta; Šimura, Jan; Yassin, Zakiya; Gandla, Madhavi L; Karady, Michal; Ljung, Karin; Winestrand, Sandra; et al. (The New phytologist, 2023)
Stem bending in trees induces flexure wood but its properties and development are poorly understood. Here, we investigated the effects of low-intensity multidirectional stem flexing on growth and wood properties of hybrid aspen, and on its transcriptomic and hormonal responses. Glasshouse-grown trees were either kept stationary or subjected to several daily shakes for 5 wk, after which the transcriptomes and hormones were analyzed in the cambial region and developing wood tissues, and the wood properties were analyzed by physical, chemical and microscopy techniques. Shaking increased primary and secondary growth and altered wood differentiation by stimulating gelatinous-fiber formation, reducing secondary wall thickness, changing matrix polysaccharides and increasing cellulose, G- and H-lignin contents, cell wall porosity and saccharification yields. Wood-forming tissues exhibited elevated jasmonate, polyamine, ethylene and brassinosteroids and reduced abscisic acid and gibberellin signaling. Transcriptional responses resembled those during tension wood formation but not opposite wood formation and revealed several thigmomorphogenesis-related genes as well as novel gene networks including FLA and XTH genes encoding plasma membrane-bound proteins. Low-intensity stem flexing stimulates growth and induces wood having improved biorefinery properties through molecular and hormonal pathways similar to thigmomorphogenesis in herbaceous plants and largely overlapping with the tension wood program of hardwoods.
Keywords: celulosa; flexure wood; mechanostimulation; dřevo; Populus; Cellulose; Wood; polysacharidy; regulace genové exprese u rostlin; wood development; polyaminy; buněčná stěna; Cell Wall; polyamines; Gene Expression Regulation, Plant; saccharification; Polyamines; Polysaccharides; Populus tremula × tremuloides; jasmonic acid signaling; thigmomorphogenesis